A Greene Country Towne Philadelphia's Ecology in the Cultural Imagination - Braddock, Alan C.; Braddock, Alan C.; Farland, Maria; Gabriel, Nate; Hansen, Andrea L. M.; Hicks, Scott; Igoe, Laura Turner; Igoe, Laura Turner; Mackintosh, Michael Dean; Menzer, Amy E.; Nepa, Stephen; Ott, John; et al. (Penn State University Press, 2021)
An unconventional history of Philadelphia that operates at the threshold of cultural and environmental studies, A Greene Country Towne expands the meaning of community beyond people to encompass nonhuman beings, things, and forces.By examining a diverse range of cultural acts and material objects created in Philadelphia-from Native American artifacts, early stoves, and literary works to public parks, photographs, and paintings-through the lens of new materialism, the essays in A Greene Country Towne ask us to consider an urban environmental history in which humans are not the only protagonists. This collection reimagines the city as a system of constantly evolving constituents and agencies that have interacted over time, a system powerfully captured by Philadelphia artists, writers, architects, and planners since the seventeenth century. In addition to the editors, contributors to this volume are Maria Farland, Nate Gabriel, Andrea L. M. Hansen, Scott Hicks, Michael Dean Mackintosh, Amy E. Menzer, Stephen Nepa, John Ott, Sue Ann Prince, and Mary I. Unger
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jul 2021)
Keywords: HISTORY / United States / State & Local / Middle Atlantic (DC, DE, MD, NJ, NY, PA)